The Integration of a Dual-Wavelength Super Pulsed Diode Laser for Consistent Tissue Ablation in the Esthetic Zone: A Case Series - Nur Hafizah Kamar Affendi; Rohana Ahmad; Farhad Vahidi; Mohd Zulkifli Hassan; Siti Nadia Rahimi (Case Reports in Dentistry)
Introduction. A diode laser is one of the universally compact accepted laser systems used fundamentally for soft tissue applications. Most diode laser devices have a single wavelength of either 810 nm for superior coagulation or 980 nm for tissue ablation. In these case series, the use of dual wavelengths (810 nm and 980 nm) in combination with super pulsing has provided a cleaner cut (no charring) with faster healing that eases the placement of the final restoration in the esthetic zone. Case Description. The present case series describe four cases in the esthetic zone that achieved hemostasis ablation without collateral damage to enhance gingival balance of definitive restoration. The gingivoplasty and gingivectomy modes are used to achieve efficient tissue ablation. Although there is no specific mode indicated in the FDA laser requirement for gingival depigmentation, the procedure could be safely performed with the dual-wavelength diode laser Result. All four patients revealed a good esthetic outcome and reported no pain postoperatively. Healing was uneventful, and definitive restoration was delivered within two to four weeks postoperatively. Conclusion. Within the limitation of these case series, the dual-wavelength super pulsed diode laser has the capacity to deliver peak powers resulting in efficient cutting and less tissue charring and also as an alternative tool for removal of gingival pigmentation. Prospective clinical research with larger sample size is needed for conclusive results.